SOSIALISASI SISTEM INTERVENSI BERBASIS AI UNTUK MENGELOLA TANTRUM ANAK AUTISME DI SLB AUTIS TALANG KELAPA PALEMBANG - Nyayu Latifah Husni; Masayu Anisah; Abdurrahman; Selfi Nurhaliza; Deden Lasmana; Dewi Permata Sari (Politeknik Negeri Sriwijaya, 2024)
This community service activity aims to introduce an artificial intelligence (AI)-based intervention device for managing tantrums in children with autism at SLB Autis Talang Kelapa Palembang. Tantrums in children with autism are often caused by their inability to express emotions, which can disrupt the learning process and affect their surrounding environment. Through the socialization of an AI device utilizing MediaPipe technology, teachers and staff were trained to quickly detect early signs of tantrums and provide interventions in the form of music designed to calm autistic children. The results of this activity indicate improved understanding among teachers, staff, and parents in detecting and responding to tantrums more effectively. The implementation of this device has been proven to reduce both the frequency and intensity of tantrums, thereby creating a more conducive learning environment for children with autism.